2011
DOI: 10.1016/j.jbi.2011.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic decision making and complexity in emergency care

Abstract: In critical care environments such as the emergency department (ED), many activities and decisions are not planned. In this study, we developed a new methodology for systematically studying what are these unplanned activities and decisions. This methodology expands the traditional naturalistic decision making (NDM) frameworks by explicitly identifying the role of environmental factors in decision making. We focused on decisions made by ED physicians as they transitioned between tasks. Through ethnographic data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 31 publications
0
36
0
1
Order By: Relevance
“…All of these behaviours will have (largely) detrimental effects on their ability to make decisionsand particularly the ability to create and choose between a wide range of options. At the same time, the physical element of stress (including effects on sleep, nutrition, and self-care) can affect the ability to make decisions over a period (Zhang et al 2002;Franklin et al 2011;Coombs et al 2016;Comes 2016) and lead to emergency managers 'collaps[ing] from exhaustion or becom[ing] inefficient in their decision-making and other areas of responsibility' (Quarantelli 1988: 380).…”
Section: High Levels Of Stressmentioning
confidence: 99%
“…All of these behaviours will have (largely) detrimental effects on their ability to make decisionsand particularly the ability to create and choose between a wide range of options. At the same time, the physical element of stress (including effects on sleep, nutrition, and self-care) can affect the ability to make decisions over a period (Zhang et al 2002;Franklin et al 2011;Coombs et al 2016;Comes 2016) and lead to emergency managers 'collaps[ing] from exhaustion or becom[ing] inefficient in their decision-making and other areas of responsibility' (Quarantelli 1988: 380).…”
Section: High Levels Of Stressmentioning
confidence: 99%
“…Studies also identify practitioner workload, resource demand and team communication as influencing clinical decisions, particularly in critical care settings. The sequence and nature of decisions can even be influenced by factors such as the physical layout of the unit and the availability of other team members [22,23]. Trainers also need to be aware that the supervisor-trainee relationship impacts on clinical decisions.…”
Section: From Decision To Action: Contextual Influencesmentioning
confidence: 99%
“…Direct observation in the emergency department (ED)61 found that only about 45% of the decisions were planned, with the rest being opportunistic or forced by interruptions. Moreover, decisions were not being made about individual patients alone, but their care within the wider view of the ED as a whole, and situational factors that defined the local, immediate demands for resources.…”
Section: Naturalistic Decision Makingmentioning
confidence: 99%